2012
DOI: 10.1007/978-3-642-33826-7_17
|View full text |Cite
|
Sign up to set email alerts
|

An Optimization Approach for Effective Formalized fUML Model Checking

Abstract: Abstract. Automatically formalizing fUML models into CSP is a challenging task. However, checking the generated CSP model using FDR2 is far more challenging. That is because the generated CSP model holds many implementation details inherited from the fUML model, as well as the formalization of the non-trivial fUML inter-object communication mechanism. Using the state space compression techniques available in FDR2 (such as Supercompilation and compression functions) is not enough to provide an effective model c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…According to the translation rule in Definition 7, the activity diagram  is first translated into the dependency structure td() = ⟨, I, T, S, C, P, F⟩ where  = {0, 1, 2, 3, 4, 5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39, i, f 1, f 2, f 3, f 4, f 5}, I = {{i}}, T = {({i}, {0}), ({0}, {3}), ({0}, {1}), ({1}, {2}), ({2}, {4}), ({2}, {8}), ({4}, {7}), ({7, 8}, {11}), ({3}, {5}), ({5}, {6}), ({6}, {f 1}), ({5}, {9}), ({9}, {10}), ({11}, {12}), ({12}, {13}), ({13}, {f 2}), ({12}, {14}), ({14}, {15}), ({15}, {16}), ({16}, {18}), ({18}, {f 3}), ({16}, {2}), ({15}, {17}), ({17}, {19}), ({10}, {20}), ({19}, {20}), ({20}, {21}), ({20}, {22}), ({21, 22}, {23}), ({23}, {24}), ({24}, {27}), ({27}, {29}),({29}, {30}),({29}, {31}),({30}, {28}),({30}, {25}),({28}, {26}),({26}, {25}), ({25}, {f 4}), ({31}, {20}), ({31}, {32}), ({32}, {33}), ({32}, {36}), ({33}, {34}), ({33}, {35}), ({34, 35}, {37}), ({37}, {38}), ({36}, {39}), ({38}, {39}), ({39}, {f 5})}, S = {{7, 8}, {21, 22}, {34, 35}}, C = {{1, 3}, {6, 9}, {13, 14}, {16, 17}, {25, 28}, {20, 32}, {33, 36}}, P = ∅, and F = {{f 1}, {f 2}, {f 3}, {f 4}, {f 5}}.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…According to the translation rule in Definition 7, the activity diagram  is first translated into the dependency structure td() = ⟨, I, T, S, C, P, F⟩ where  = {0, 1, 2, 3, 4, 5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39, i, f 1, f 2, f 3, f 4, f 5}, I = {{i}}, T = {({i}, {0}), ({0}, {3}), ({0}, {1}), ({1}, {2}), ({2}, {4}), ({2}, {8}), ({4}, {7}), ({7, 8}, {11}), ({3}, {5}), ({5}, {6}), ({6}, {f 1}), ({5}, {9}), ({9}, {10}), ({11}, {12}), ({12}, {13}), ({13}, {f 2}), ({12}, {14}), ({14}, {15}), ({15}, {16}), ({16}, {18}), ({18}, {f 3}), ({16}, {2}), ({15}, {17}), ({17}, {19}), ({10}, {20}), ({19}, {20}), ({20}, {21}), ({20}, {22}), ({21, 22}, {23}), ({23}, {24}), ({24}, {27}), ({27}, {29}),({29}, {30}),({29}, {31}),({30}, {28}),({30}, {25}),({28}, {26}),({26}, {25}), ({25}, {f 4}), ({31}, {20}), ({31}, {32}), ({32}, {33}), ({32}, {36}), ({33}, {34}), ({33}, {35}), ({34, 35}, {37}), ({37}, {38}), ({36}, {39}), ({38}, {39}), ({39}, {f 5})}, S = {{7, 8}, {21, 22}, {34, 35}}, C = {{1, 3}, {6, 9}, {13, 14}, {16, 17}, {25, 28}, {20, 32}, {33, 36}}, P = ∅, and F = {{f 1}, {f 2}, {f 3}, {f 4}, {f 5}}.…”
Section: Figurementioning
confidence: 99%
“…The study revealed interesting insights into the semantic expressivity of activity diagrams and the semantic nature of the different modeling elements, in particular, of the object nodes and the activity final nodes. Abdelhalim et al defined a method of transforming the state machine diagrams and activity diagrams into communicating sequential processes. Later, the method used a model checker to verify the resulting communicating sequential process representation.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation